Islamic Philosophical Perspectives on Social Cohesion: Revisiting Classical Thought to Address Fragmentation in Post Digital Muslim Communities - Syarifudin Syarifudin; Aan Kudrotulloh; Ade Imun Romadan (International Forum of Researchers and Lecturers, 2025)
This study examines the convergence between classical Islamic philosophy and contemporary digital theory, emphasizing how foundational Islamic concepts can respond to social fragmentation in post-digital Muslim societies. As digital technologies increasingly mediate religious learning, identity formation, and communal interaction, Muslim communities face growing challenges, including the weakening of social bonds and the decentralization of religious authority. Online platforms encourage individualized interpretations of faith and pluralistic expressions of religiosity, which, while expanding participation, often contribute to fragmented identities and diminished communal cohesion.Drawing upon core classical concepts such as ummah (community), akhlaq (ethics), and asabiyya (social solidarity), this research argues that Islamic intellectual heritage offers a normative framework capable of addressing these disruptions. These concepts underscore collective responsibility, moral discipline, and the cultivation of shared values as the foundation of a stable and just society. Using a qualitative approach grounded in textual analysis of classical Islamic scholarship and contemporary digital sociology, the study recontextualizes these principles within present-day digital environments.The findings suggest that adapting traditional values to online engagement can strengthen ethical conduct, mutual accountability, and constructive dialogue in virtual spaces. The notion of a “cyber ummah” further illustrates how transnational digital networks may foster solidarity across geographic and ideological boundaries. Ultimately, this study affirms the continuing relevance of classical Islamic philosophy in guiding the development of an inclusive, morally grounded, and socially cohesive digital society.